Effect of NPK application on rooibos (Aspalathus linearis) under Clanwilliam field conditions - Lourenco, Marcello Rufino (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScAgric)--Stellenbosch University, 2018.